Conflict Dissolution by Reframing Game Payoffs using Linear Perturbations - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 1983)
Human beings have a prevailing drive to achieve their self-interest goals or equilibrium states, which may subsume their social interests. An ideal working environment or cooperative game situation would be one in which each participant or player maximizes his/her own interest while maximizing his/her contribution to the collective group interest. This paper addresses the feasibility, methods, and bounds for reframing a general n-person game into an ideal game in which full cooperation or a targeted solution can be induced and maintained by the players' self-interest maximization. Criteria for good reframing are introduced. Monotonic games, self-interest cooperative and noncooperative games, and a decomposition theory of general games are also introduced to facilitate the study. It is shown that everyn-person game can be written as the sum of a self-interest cooperative game and a self-interest noncooperative game. Every n-person game can be reframed so that full cooperation can be achieved by the players' self-interest maximization. Every n-person game can be reframed so that a targeted solution can be obtained and maintained through the players' self-interest maximization.